Exploring the stress of olympic postponement due to COVID-19 on elite/international and world-class parenting and pregnant runners - Francine E. Darroch; Sydney V. M. Smith; Madeleine D. Sheppard-Perkins; Audrey R. Giles; Dylan Wykes (Frontiers Media S.A., 2023)
The primary objective of this community-based participatory research is to explore the impacts of COVID-19 and the delayed Tokyo 2020 Olympic Games on world-class and elite/international-class parenting and pregnant athletes. Participants in this study include 11 female and 10 male parenting and/or pregnant middle and distance runners. Combined, the participants have competed at 26 Olympic Games and 31 World Championships. Drawing on the general concepts of stressors and psychological resilience, we use thematic analysis to develop four themes to understand the stressors for world-class and elite/international-class parenting and pregnant athletes due to COVID-19 and the delayed Tokyo 2020 Olympic Games: (1) lack of childcare support, (2) family planning, and (3) needing to stay away from sources of COVID-including their children. Despite the stressors identified in the aforementioned themes, we identified a fourth theme: (4) participants demonstrated adaptability to stress in spite of-or due to-their athlete-parent identities.